CR리츠를 활용한 미분양 주택 유동화 지원정책 분석 - 시스템다이내믹스를 이용하여 - 나호준; 박문서; 이현수; 황성주; Na, Ho-Jun; Park, Moonseo; Lee, Hyun-Soo; Hwang, Sungjoo (한국건설관리학회 논문집, 14(5), 2013)
Unsold new houses have increased before the financial crisis, and have steadily accumulated since domestic diffusion ratio of house exceeded 100%. From a long term point of view, it is important to liquidate unsold new houses and raise funds from the capital market till the housing market recovers because the accumulation of unsold new houses is a financial burden to the construction company and for that reason, the housing policies to support the liquidity of unsold new houses must be consistently available means. Therefore, the purpose of this study is to analyze the effectiveness of government's policy to support the liquidity of unsold new houses using CR-REITs from among these policies with system dynamics. Using the system dynamics model, this study finds the significance and limitation of the policy to liquidate unsold new houses using CR-REITs and suggests the measures to improve the policy. 최근 미분양 주택의 발생은 글로벌 금융위기와 내수경기 침체로 본격화되었으며, 주택보급률이 100%를 넘는 현 상황에서는 향후에도 언제든지 미분양 주택 적체가 심화될 수 있다. 정부는 이러한 미분양 주택 적체를 해결하기 위하여 여러 대책들을 수립 시행해 왔으며, IMF 외환위기 이후 부동산 금융시장의 발전을 배경으로 미분양 주택 유동화 대책이 시행되게 되었다. 또한, 2008년 이후 급격히 증가한 준공 후 미분양 주택은 단기간에 해결하기가 쉽지 않으며, 이로 인한 건설사의 유동성 위기를 해결하기 위해서는 미분양 주택을 유동화시킴으로써 자본시장으로부터의 자금 유입을 원활하게 하는 것이 중요하다. 따라서 본 연구에서는 정부의 미분양 주택 유동화 대책 중 최근 몇 년간 가장 문제가 되어온 중대형의 준공 후 미분양 주택을 해결할 수 있는 기업구조조정 리츠(CR-REITs)를 활용한 정책의 실효성을 시스템 다이내믹스를 이용하여 분석하고 개선방안을 제시하고자 한다.